2000
DOI: 10.1016/s1044-0305(99)00141-5
|View full text |Cite
|
Sign up to set email alerts
|

In-source decay of hyperbranched polyesteramides in matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Hyperbranched polyesteramides (DA2), prepared from hexahydrophthalic anhydride (D) and diisopropanolamine (A) have been characterized, by use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS), field desorption (FD)-MS, and electrospray ionization (ESI)-MS. MALDI of polyesteramides produces protonated molecules. The spectra show a complex chemical composition distribution and end-group distribution which are mainly composed of two series of homologous oligomers DnA(n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…Other minor peak series in Figure 6 can be ascribed to the byproduct arising from the side reactions during RAFT polymerization, 44,45 fragmentation of polymer chain and dithioester moiety by MALDI-generated ions. [46][47][48][49] These results clearly showed that the CPDN moieties were attached at polymer chain ends. The molecular weight of PMMA by MALDI-TOF mass spectra, was 4.77 Â 10 3 g/mol (M w /M n = 1.16), which was much smaller than the GPC value (M n,GPC = 9.81 Â 10 3 g/mol, PDI = 1.20).…”
Section: Resultsmentioning
confidence: 99%
“…Other minor peak series in Figure 6 can be ascribed to the byproduct arising from the side reactions during RAFT polymerization, 44,45 fragmentation of polymer chain and dithioester moiety by MALDI-generated ions. [46][47][48][49] These results clearly showed that the CPDN moieties were attached at polymer chain ends. The molecular weight of PMMA by MALDI-TOF mass spectra, was 4.77 Â 10 3 g/mol (M w /M n = 1.16), which was much smaller than the GPC value (M n,GPC = 9.81 Â 10 3 g/mol, PDI = 1.20).…”
Section: Resultsmentioning
confidence: 99%
“…It is proposed that the fragment ions seen in the TOF measurements could well be short-lived ions that do not survive for the requisite length of time to be observed by FTMS. Observation of low mass fragment ions is not uncommon in TOF-MS [26,27], as "prompt fragmentation" can occur in the ion-source region. Furthermore, in delayed extraction ion sources (employing time-lag energy focusing), fast metastable fragmentation might occur during the delay time before extraction (on the 100 to 1200 ns time scale).…”
Section: Resultsmentioning
confidence: 99%
“…PSD‐MALDI has been used successfully in biopolymer characterization,19–29 but has been used less extensively for synthetic polymers, reasonably on account of the enhanced complexity of the samples involved. PSD‐MALDI‐TOF analysis has been performed to study polymers such as polycarbonate,30 polyurethanes,31 polyamides,32 polyesters,33 and polyesteramides 34, 35…”
mentioning
confidence: 99%